ДОСЛІДЖЕННЯ ЕНЕРГОЕФЕКТИВНОСТІ ЕЛЕКТРОМЕХАНІЧНОЇ СИСТЕМИ ВОДОПОСТАЧАННЯ БАГАТОПОВЕРХОВОГО БУДИНКУ ІЗ ДВОРІВНЕВИМИ СТОЯКАМИ - Попович, О.М.; Яшин, Р.В. (Інститут електродинаміки НАН України, Київ, 2023)
The influence of the structure of the electromechanical water supply system of a multi - storey building on its energy efficiency is investigated. A quantitative estimate of the reduction in the efficiency of the system compared to the supply of water to the top floor, depending on the number of floors. A complex mathematical model of the system with one and two risers (asynchronous motor - pump - branched hydraulic network) with determination of parameters of operating modes taking into account the mutual influence of system components is developed. The value of the system efficiency criterion as the ratio of the potential energy of water at the consumer to the consumed energy is substantiated and quantified. The electromechanical water supply system of a multi-storey building with two levels of risers consumes 30% less energy than the system with a single riser, due to the reduction of the amount of excess pressure in consumers of lower floors. References 12, figures 3, table 1.